Strategi Komunikasi Guru Terhadap Siswa Berkebutuhan Khusus Disekolah Alam Karawang - Widiyawati, Sefti; Oktariani Lubis, Fardiah (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the communication strategies implemented by teachers towards students with special needs (ABK) at Sekolah Alam Karawang. Effective communication is key in the inclusive learning process, especially when teachers face very diverse student characteristics. This study uses a qualitative approach with a descriptive method. Data were obtained through in-depth interviews, direct observation, and documentation. By describing the results of the interviews conducted, data analysis techniques were carried out. The communication strategies implemented by teachers towards students with special needs at Sekolah Alam Karawang are factors that are considered. The results of the study indicate that teacher communication strategies include three main aspects: communicator strategies, media strategies, and message delivery strategies. Communicator strategies are carried out through the planning stages, student character recognition, and mentoring by shadow teachers. Media strategies use concrete aids and experience-based activities to stimulate students' sensory. Message delivery strategies are carried out with a one-way instruction approach, repetition, and the use of simple and slow language. Evaluation of this strategy is carried out weekly through weekly reports and plans, and involves stimulus managers and psychologists if serious obstacles are found